2006
DOI: 10.1002/jbm.b.30600
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid–phosphate glass composite foams as scaffolds for bone tissue engineering

Abstract: Phosphate glass (PG) of the composition 0.46(CaO)-0.04(Na(2)O)-0.5(P(2)O(5)) was used as filler in poly-L-lactic acid (PLA) foams developed as degradable scaffolds for bone tissue engineering. The effect of PG on PLA was assessed both in bulk and porous composite foams. Composites with various PG content (0, 5, 10, and 20 wt %) were melt-extruded, and either compression-molded or foamed through supercritical CO(2). Dynamic mechanical analysis on the bulk composites showed that incorporating 20 wt % PG resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…Ruhe et al (2005b) showed bioactive factors to be incorporated into (PLGA/ Ca-P cement) composites and could be slowly released. Furthermore, the combination of osteogenic growth factor release (BMP-2) from polymer scaffolds such as PLA and the addition of preosteogenic cells have further increased the possibility of engineering bone (Rose et al, 2004;Yang et al, 2004;Montjovent et al, 2005;Montjovent et al, 2007;Georgiou et al, 2007), whilst Jansen et al (2005) demonstrated orthotopic bone formation in a rabbit cranial defect model stimulated in rhTGFβ1 and rhBMP-2 CaP cement and Titanium-fibre mesh scaffolds.…”
Section: Skeletal Tissue Engineering the Clinical Need For New Bonementioning
confidence: 99%
“…Ruhe et al (2005b) showed bioactive factors to be incorporated into (PLGA/ Ca-P cement) composites and could be slowly released. Furthermore, the combination of osteogenic growth factor release (BMP-2) from polymer scaffolds such as PLA and the addition of preosteogenic cells have further increased the possibility of engineering bone (Rose et al, 2004;Yang et al, 2004;Montjovent et al, 2005;Montjovent et al, 2007;Georgiou et al, 2007), whilst Jansen et al (2005) demonstrated orthotopic bone formation in a rabbit cranial defect model stimulated in rhTGFβ1 and rhBMP-2 CaP cement and Titanium-fibre mesh scaffolds.…”
Section: Skeletal Tissue Engineering the Clinical Need For New Bonementioning
confidence: 99%
“…This was carried out for a PDLLA scaffold that had a spherical architecture, with a pore size of 300µm and porosity of 90% (Blecha et al 2010;Bose et al 2013;Georgiou et al 2007;Karande et al 2004;Silva et al 2006;Tan et al 2011). Firstly, we investigated the influence of inlet fluid velocity on the WSS using the similar FSI model to that described in Section 2.4.…”
Section: Combined Loadingmentioning
confidence: 99%
“…Haimi et al [55] cultured human adipose stem cells on PLA reinforced with between 0 and 20 wt% of either β-TCP or a bioactive glass based on 5%Na 2 O-7.5%K 2 O-3%MgO-25%CaO-59.5%SiO 2 with porosity produced by freeze drying. After 2 weeks, compared to nonreinforced PLA scaffolds, statistically more cells were seen on the scaffolds reinforced with β-TCP and statistically less on the scaffolds reinforced with the bioactive glass.…”
Section: In Vitro Testing Of Scaffoldsmentioning
confidence: 99%